(untitled) (PANGEEA, 2025)
Adopting a smart water monitoring system must go beyond simply automating the reading and reporting of recorded flows and pressures. In order to know the water consumption of users in depth and to achieve a system capable of carrying out commercial and operational management, it is also necessary to combine other factors with automation, namely information technology, database science and other analytical skills. In the present work, the study object was the water supply system of Miroslava commune. The Miroslava water supply system has as source the Iasi City distribution network. The capacity of the source is sufficient for a proper water supply to the system. The drinking water supply of Miroslava commune is a mixed one: from the Miroslava 5000 cubic meters water tank by gravity and also by pumping. The quality of flow meters and network pressure are relevant parameters for determining water consumption. In order to cope with an intermittent water demand, many water distribution networks, like the one in the case studied, include storage tanks, which allow users to store water during off-peak hours. This random consumption pattern can lead to longer residence times in the lateral pipes of distribution networks, which can negatively affect the quality of water reaching end users. The use of water for purposes other than domestic ones (irrigation systems, filling of swimming pools, using water to wash concrete surfaces inside properties, etc.) leads to an increase in consumption beyond the maximum designed capacity of the water supply system, which causes difficulties in ensuring a minimum level of water in the tanks, which allows the pumps to operate in normal mode. Increasing the degree of consumer satisfaction by increasing the pressure in the water network is a solution that also brings drawbacks, such as increasing the mechanical stress on pipes and fittings, which leads to an increase of breakdowns frequency, additional water losses and to the deterioration of environmental conditions.